P245 Whole blood levels of microrna-34a predict survival and regulate genes associated with pulmonary arterial hypertension. (15th November 2016) - Lin, J; Iremonger, J; Pickworth, J; Rothman, A; Casbolt, H; Arnold, N; Elliot, C; Condliffe, R; Kiely, D; Lawrie, A
Abstract : Introduction: Despite advanced therapies for pulmonary arterial hypertension (PAH), the hyperproliferative pulmonary vasculopathy persists. Circulatory microRNAs (miR) offer considerable promise as both a prognostic biomarker, and to identify molecular mechanisms underlying PAH. Previous study from our lab identified whole blood miR-34a as downregulated in patients with PAH. Objectives: To validate changes in whole blood miR-34a levels in patients with PAH and relate them to disease severity and survival, and determine the phenotypic effect on pulmonary artery smooth muscle cells (PASMC). Methods: Whole blood RNA was isolated from 27 treatment-naive patients with PAH, 12 age-matched healthy volunteers (HV) and experimental models of PAH (Monocrotaline-MCT, Sugen5416/hypoxia-SuHx and controls, n = 5/group). Whole blood miR-34a-5p and −3p levels were measured by qPCR. The phenotypic effect of miR-34a-5p and −3p levels was assessed on PASMC in-vitro . Differences between groups were determined by Student's t-test or ANOVA-Tukey. Results: Whole blood miR-34a-5p was reduced in patients with PAH (p < 0.0001) and experimental models of PAH (MCT p < 0.05, SuHx p < 0.001). Receiver operating characteristic curve identified that miR-34a-5p levels discriminates patients with PAH from HV (AUC = 0.86, p = 0.001). MiR-34a-5p levels were significantly lower in patients with severe PAH, as defined by a cardiac index of <2 vs >2.5 l/min/m 2 (p < 0.05) and NT-proBNP > 300 vs <300 ng/l (p < 0.001) and predict survival at 5 years. MiR-34a-5p levels were negatively correlated with pulmonary vascular resistance (r = −0.4, p < 0.05) and pulmonary arterial wedge pressure (r = −0.4, p < 0.05). Preliminary data showed that whole blood miR-34a-3p was reduced in patients with PAH (p = 0.0267) and experimental models of PAH (MCT p < 0.01, SuHx p < 0.01); and delineates patients with PAH from HV (AUC = 0.925, P = 0.01). Transfection of PDGF-stimulated PASMC with miR-34a-5p or −3p inhibitor promote PASMC proliferation (p < 0.001). In contrast, miR-34a-5p and −3p mimic suppress PASMC proliferation (p < 0.05 and p < 0.001 respectively). Additionally, transfection with miR-34a-3p increases caspase-3/7 activities in PASMC (p < 0.0001). Conclusions: Reduced miR-34a-5p levels associate with increased disease severity and poor prognosis in PAH. MiR-34a-5p and −3p levels regulate PASMC proliferative-phenotype in response to PDGF. This research identifies miR-34a-5p and −3p as potential biomarkers, subsequent network analysis may identify novel disease mechanisms. Further experiments in preclinical models are currently underway.